Comparison of AlxGa1−xN multiple quantum wells designed for 265 and 285 nm deep-ultraviolet LEDs grown on AlN templates having macrosteps. (4th June 2019) - Nagasawa, Yosuke; Kojima, Kazunobu; Hirano, Akira; Ipponmatsu, Masamichi; Honda, Yoshio; Amano, Hiroshi; Akasaki, Isamu; Chichibu, Shigefusa F.
Abstract: AlGaN multiple quantum wells (MQWs) targeting 265 and 285 nm deep-ultraviolet LEDs grown on AlN templates with macrosteps were compared. In the cathodoluminescence images of the 285 nm MQW, high-intensity zones were observed along the edgelines of the macrosteps with wavelengths of 290–296 nm and on the terraces with wavelengths of 286–288 nm. Dark spots related to threading dislocations were seen in the entire 285 nm MQW. For 265 nm, high-intensity zones were limited along the edgelines and dark spots showed a low-contrast, which is likely to be caused by nonradiative recombination centers due to point defects.